Enterobacter soli Strain AF-22b-4245: Study of the Genome and the Effect on Wheat Growth - Ekaterina Alexeevna Sokolova; Olga Viktorovna Mishukova; Inna Viktorovna Khlistun; Irina Nikolaevna Tromenschleger; Evgeniya Vladimirovna Chumanova; Elena Nikolaevna Voronina (Microbiology Research)
Background: In this work the plant growth-promoting (PGP) qualities of the Enterobacter soli strain AF-22b-4245 were studied, including screening tests for PGP, whole genome sequencing (WGS) and genome annotation, and greenhouse experiments on wheat. A gene table was formed that allows us to evaluate the potential PGP properties of a microorganism based on the results of genome-wide sequencing. Results: Based on the results of screening tests and genome annotation, it can be concluded that the E. soli strain AF-22b-4245 strain may have PGP properties, which consist in the ability to survive in arid and saline soils contaminated with copper, arsenic, lead, and chromium soils, form biofilms, produce phytohormones, siderophores, and solubilize phosphorus. Based on the results of experiments on wheat, the E. soli strain AF-22b-4245 increases the efficiency of mineral fertilizers; this effect persists even in conditions of drought and excess salt. It has been shown that E. soli A F22b-4245 can compensate for the lack of soluble phosphorus in the mineral fertilizer, probably by solubilizing insoluble forms in the soil.